Age‐related changes in the morphology and the distribution of IgA and IgG in the pharyngeal tonsils of yaks (Bos grunniens). (20th December 2018) - Xu, Yuanfang; Sun, Juan; Cui, Yan; Yu, Sijiu; He, Junfeng; Liu, Penggang; Zhang, Qian
Abstract: To evaluate age‐related changes in the morphology as well as the expression and localization of IgA and IgG in yak pharyngeal tonsils, 20 healthy yaks were divided into four age groups [newborn (1–7 days old), juvenile (5–7 months old), adult (3–6 years old) and old (7–10 years old)]. Morphologic characteristics were observed by histological techniques. The expression and localization of IgA and IgG in pharyngeal tonsils were detected by enzyme linked immunosorbent assay (ELISA) and immunohistochemistry, respectively. The results showed that the epithelium of the pharyngeal tonsils included nonreticular epithelium with an intact basement membrane and reticular epithelium with a discontinuous basement membrane and nonepithelial cell infiltration. In newborn yaks, only primary lymphoid follicles were observed in pharyngeal tonsils. In other age groups, both primary and secondary lymphoid follicles were observed, but some of the lymphoid follicles in the old yaks were degenerated. The number of lymphoid follicles increased from the newborn to the adult group and peaked in the adult group, but the number decreased in the old group. In addition, the age‐related trends of IgA and IgG protein expression were similar to those of the number of lymphoid follicles. The concentration of IgG was significantly higher than that of IgA in all age groups. Both IgA and IgG antibody secreting cells (ASCs) were distributed in the subepithelial region of the nonreticular epithelium, the reticular epithelium, the lymphoid follicles, the interfollicular areas and in between the salivary glands. The densities of IgA and IgG ASCs in pharyngeal tonsils were similar to the expression trend of both proteins in each age group. The results indicate that the morphology and amount of lymphoid follicles in yak pharyngeal tonsils vary with age. Pharyngeal tonsils produce more IgG than IgA, indicating that IgG could be significant component of mucosal immune responses in yaks. Abstract : Pharyngeal tonsil of an old yak that consisted of epithelium (E) with crypts (C) and the parenchyma, in which there were not only primary and secondary lymphoid follicles (SF), but also degenerated lymphoid follicles (DF). HE. Bar = 500 μm.